Tandem Mass Tag-Based Quantitative Proteomic Analysis of Chicken Bursa of Fabricius Infected With Reticuloendotheliosis Virus - Yang, Dahan; Lv, Xiaoping; Zhang, Shujun; Zheng, Shimin (Frontiers in Veterinary Science, 2021)
Reticuloendotheliosis virus (REV) is a type C avian retrovirus; which causes immunosuppression, dwarf syndrome, and lymphoma in infected hosts. In this study, we used tandem mass tag (TMT) labeling and liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) to characterize protein alterations in chicken bursa of Fabricius, before and after REV infection at 7, 14, 21, and 28 days. Our data showed that 1127, 999, 910 and 1138 differentially expressed proteins were significantly altered at 7, 14, 21, 28 days after REV infection, respectively. Morphological analysis showed that REV infection reduced in cortical lymphocytes, bursal follicles atrophys and nuclear damage. Bioinformatics analysis indicated these proteins were mainly involved with immune responses, energy metabolism, cellular processes, biological regulation, metabolic processes, response to stimuli, and multicellular organismal process. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway cluster analysis showed that post-infection, proteins were enriched in the cell cycle, Wnt signaling, antigen processing and presentation, cytokine receptor interaction, adenosine 3',5'-cyclic monophosphate signaling pathway, and NF-κB signaling. In addition, We observed that peroxiredoxin 4 (PRDX4), peroxiredoxin 6 (PRDX6), glutathione peroxidase 3 (GPX3), catalase (CAT), and peroxidasin (PXDN) were involved in oxidative stress. Some heat shock protein (HSP) family members such as HSPH1, DNAJA4, HSPA8, HSPA4L also changed significantly after REV infection. These findings help clarify interactions between REV and the host, and provides mechanistic insights on REV-induced host immunosuppression.